DEIXIS ANALYSIS OF THE LYRICS IN THE SONGS OF THE “KLANG” ALBUM BY ENGLISH BAND “THE RAKES” - Rananta, Naufal Farrel (Jurnal Bahasa Asing, 2025)
Language is a process that is only in humans which is not instinctive in sharing ideas. Music is considered a language, and music also contains meanings or messages encoded by the speaker. Deixis are expressions that require context from the discourse participants. Person deixis are deictic expressions that require context of people to understand the context. “Klang” is a music album by the British band “The Rakes” released in 2009. The researcher was interested in figuring out the deixis in three songs. These songs are “1989”, “Mullers Rachet”, and “That’s the Reason”. Using the qualitative method, the researcher found that 119 person deixis were present.